Evaluating a behaviour change intervention to enhance athlete monitoring system engagement: Insights from elite sport - Neupert, E. C.; Holder, T.; Jobson, S. A. (International Journal of Sports Science & Coaching, 2025)
Athlete engagement with monitoring remains challenging, despite athlete monitoring systems (AMS) having the potential to enhance performance. Behaviour change frameworks may offer strategies to improve AMS engagement, but are underutilised in elite sport. This study assessed the practicality and utility of a behaviour change intervention (BCI) to improve AMS engagement. Three national team coaches (43.6 ± 10.0 years) and eight athletes (20.1 ± 2.0 years) participated in a six-month BCI to promote AMS adherence to daily monitoring using the Behaviour Change Wheel (BCW). All participants completed pre and post intervention semi-structured interviews, which were thematically analysed. Adherence to monitoring declined during the intervention, but the coaches reported improved athlete awareness of monitoring. Reduced adherence could be attributed to the partial implementation of the intervention caused by coaching personnel changes. In the post intervention interviews athletes indicated there was considerable intercoach variability in AMS use and feedback to athletes, frustrating both athletes and coaches. The coaches noted athletes lacked motivation and understanding of the AMS and its purpose, further hindering engagement. Overall, the use of the BCW enabled a feasible intervention to be devised, but the BCW proved cumbersome to adapt to the swift organisational changes often experienced in elite sport. Future interventions should consider ensuring a consistent and shared framework for AMS use between staff. Behaviour change targets should have contingencies for organisational changes, and focus on key interactions such as the coach/athlete relationship, its inter-relation with AMS data, and the feedback of data between the coach, athlete and practitioner.